What's in a name? Theorising the Inter-relationships of gender and violence - Boyle, Karen (2019)
This paper explores the representational practices of feminist theorising around gender and violence. Adapting Liz Kelly’s notion of the continuum of women’s experiences of sexual violence, I argue that 'continuum thinking' can offer important interventions which unsettle binaries, recognise grey areas in women's experiences and avoid 'othering' specific communities. Continuum thinking allows us to understand connections whilst nevertheless maintaining distinctions that are important conceptually, politically, legally. However, this is dependent upon recognising the multiplicity of continuums in feminist theorising – as well as in policy contexts – and the different ways in which they operate. A discussion of contemporary theory and policy suggests that this multiplicity is not always recognised, resulting in a flattening of distinctions which can make it difficult to recognise the specifically gendered patterns of violence and experience. I conclude by considering how focusing on men's behaviour might offer one way of unsettling the contemporary orthodoxy which equates gender-based violence and violence against women